Islamic Education: A Principle to Develop Religious Society to Anticipate Negative Impact of Social Media - Nasrudin, Solihin (Hunafa: Jurnal Studia Islamika, 2017)
This study aims to analyze how the Islamic education is able to be the principle of inter-religious harmony to  anticipate  negative impact of social media use. Islam as a universal religion has proven its ability  to encourage the development of science and technology. Social media has emerged along with the development of information technology. The social media is able to facilitate  community to communicate and  to exchange information, but at the same time social media may also threat the harmony of interfaith relationship. This is due to the misuse of social media by irresponsible individuals who intentionally used  social media to create conflict between religious groups. Islamic education is expected to be a foundation to create society with good morale and ethics. This will also produce society  with good manner in using social media to avoid negative impact and to create  harmony among society and religions Indonesia.